The Physics of Small Molecule Acceptors for Efficient and Stable Bulk Heterojunction Solar Cells. Issue 12 (29th January 2018) - Gasparini, Nicola; Wadsworth, Andrew; Moser, Maximilian; Baran, Derya; McCulloch, Iain; Brabec, Christoph J.
Abstract: Organic bulk heterojunction solar cells based on small molecule acceptors have recently seen a rapid rise in the power conversion efficiency with values exceeding 13%. This impressive achievement has been obtained by simultaneous reduction of voltage and charge recombination losses within this class of materials as compared to fullerene‐based solar cells. In this contribution, the authors review the current understanding of the relevant photophysical processes in highly efficient nonfullerene acceptor (NFA) small molecules. Charge generation, recombination, and charge transport is discussed in comparison to fullerene‐based composites. Finally, the authors review the superior light and thermal stability of nonfullerene small molecule acceptor based solar cells, and highlight the importance of NFA‐based composites that enable devices without early performance loss, thus resembling so‐called burn‐in free devices. Abstract : In this contribution, the authors review the current understanding of the relevant photophysical processes, as well as the superior light and thermal stability of efficient nonfullerene acceptor small molecules in comparison to fullerenes‐based composites.